The nörlund orlicz spaces of entire sequence - Subramanian, N.; Altin, Y.; Bektaş, Ç. (Walter de Gruyter GmbH, 2007)
Let ?M denote the space of all Orlicz space entire sequences. Let ?M denote the spaces of all Orlicz space of analytic sequences. This paper is devoted to a study of the general properties of Nörlund Orlicz sequence space ?( ?M ) and ?M. © 2007 Warsaw University. All rights reserved.
Keywords: Analytic sequences; Barreled space; Entire sequences; Orlicz sequences; Semi reflexive spaces